AKTIVITAS ANTIBAKTERI TEPUNG CACING TANAH (Lumbricus rubellus) TERHADAP Enterococcus faecalis SECARA IN VITRO - Ridha Andayani; Zaki Mubarak; Dian Rizki Rinanda (Dentistry Faculty, 2016)
AbstractEnterococcus faecalis is a facultative anerobic bacterium which can causesecondary periapicalinfection and is very resistant to numerous antimicrobial substances normally used during the rootcanal treatment. Earthworm (Lumbricusrubellus) possess antimicrobial peptide, known as Lumbricin-1 which is known tohinder the growth of Gram positive and Gram negative bacteria as well as fungi,but rarely caused resistance. This research was an experimental laboratory study conducted to observethe antibacterial activity of Lumbricin-1 contained in earthworm powder towards the growth of E.faecalis in vitro. Enterococcusfaecalis was cultured on CHROMagar VRE media and incubatedanaerobically for24-48 hours in the temperature of 37C. The bacterium was identified by observingthe colour of the colony of the bacterium growing on the CHROMagarVRE medium and Gramstaining, while antibacterial activity test was performedusing disk diffusion method. Statisticalanalysis using one way ANOVA and Duncan test showed that there was a significant difference (p 0,05) between test and control group. The result of the study showed that earthworm powderpossessed strong antibacterial activity towards the growth of Enterococcusfaecalis.Key words: Enterococcus faecalis, Lumbricus rubellus, antimicrobial peptide, Lumbricin-1